1981
DOI: 10.1177/028418518102200506
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Computer Tomography in the Evaluation of Focal Liver Disease

Abstract: The results of ultrasound and computer tomography in 150 patients with possible focal liver disease were compared. Ultrasound was more sensitive than CT in detecting lesions but similar information on the nature of the lesions was obtained with both methods. CT provided more complete information than US on the extent of the lesion. Thus, CT and US are supplementary in the evaluation of focal liver disease. Because of the higher sensitivity US should be the first examination, followed, if clinically indicated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…It is of the utmost importance that a focal liver lesion is visualized with the greatest accuracy. Scintigraphy (Christensen, Jacobsen & Johansen 1982) has been used for that purpose, but CT scanning (Bartolozzi et al. 1981al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is of the utmost importance that a focal liver lesion is visualized with the greatest accuracy. Scintigraphy (Christensen, Jacobsen & Johansen 1982) has been used for that purpose, but CT scanning (Bartolozzi et al. 1981al.…”
Section: Discussionmentioning
confidence: 99%
“…Histological fine needle biopsy (HFNB) from the liver is a rather new diagnostic method that has the potential of providing the morphological benefits of surgical biopsies (Isler et al. 1981, Wittenberg et al 1982, Lieberman, Hafez & Crummy 1982, Wernecke, Heckemann & Rehwald 1984, Torp-Pedersen, Juul & Vyberg 1984.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 More recent studies, with faster total body scan times of 18 seconds and less roentgenogram diffraction by using narrower window widths, have shown CT to be equal, or superior, to US and RN scans in evaluating hepatic neoplasms. [7][8][9][10] Cancer patients receiving hepatic resection or transplantation are an ideal population in which to study the accuracy of hepatic-imaging techniques. The imaging procedure in this setting is usually done shortly before the operative procedure.…”
Section: Discussionmentioning
confidence: 99%
“…6 In a comparative study of US and CT in the evaluation of focal liver disease, US was found to be more sensitive but CT had higher specificity and provided more information about intrahepatic masses and extrahepatic disease, if present. 7 Overall, when compared to either US or RN scans, CT is presently considered to be the single best examination to determine both the presence and the extent of space-occupying lesions within the liver. [8][9][10] CT scanning, therefore, has become an accepted method for defining tumor response to treatment.…”
mentioning
confidence: 99%